2003
DOI: 10.1046/j.1365-2141.2003.04742.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of mitochondrial targeting in arsenic trioxide‐induced apoptosis in myeloid cell lines

Abstract: Summary Data regarding the role of mitochondria in arsenic trioxide (As2O3)‐induced apoptosis are controversial. We investigated the contribution of caspases and mitochondrial depolarization to As2O3‐induced apoptosis in the myeloid cell lines NB‐4, HL‐60 and U‐937. Caspase inhibition reduced the amount of cells with As2O3 (20 μmol/l)‐induced mitochondrial depolarization by about 50% in all cell lines. As2O3 also induced dose‐dependent phosphatidylserine exposure in cells without depolarized mitochondria. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…It is well known that mitochondria play a critical role in initiating apoptotic cell death (Körper et al ., 2004). Therefore, we searched for HB2‐induced mitochondrial alterations related to Δ Ψ m and O 2 •− accumulation either in the absence or presence of DQA.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that mitochondria play a critical role in initiating apoptotic cell death (Körper et al ., 2004). Therefore, we searched for HB2‐induced mitochondrial alterations related to Δ Ψ m and O 2 •− accumulation either in the absence or presence of DQA.…”
Section: Discussionmentioning
confidence: 99%
“…As 2 O 3 has been shown to down-regulate the levels of the oncogene fusion protein bcr-abl, and this is thought to contribute to its ability to act against promyelocytic leukaemia [42]. Its toxicity has also been shown to depend upon the cellular reduced glutathione levels, and agents that deplete GSH can enhance As 2 O 3 toxicity [43,44]. A synergistic effect of extracellular ascorbate has been documented, and this is now thought to be due to the depletion of intracellular GSH by high extracellular concentrations of ascorbate via the production of H 2 O 2 in the culture medium, leading to apoptosis [19,45].…”
Section: Introductionmentioning
confidence: 99%
“…Decrease of Ψ m was shown to play a crucial role in As 2 O 3 therapy-relevant effects [15,17]. These effects are most probably based on inhibition of enzymes of the intracellular glutathione redox system, such as glutathione peroxidase GPx [57,58], glutathione reductase GR and glutathione-S-transferase [58], resulting in an increase of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, we showed that induction of apoptosis by As 2 O 3 in 22 myeloid and non-myeloid malignant cell lines of different sensitivity for cytostatic drugs, is based on breakdown of the mitochondrial membrane potential (Ψ m ) and therefore the redox system of the cell is one of the primary targets of As 2 O 3 . Activation of caspases is a downstream effect occurring after the breakdown of Ψ m [15][16][17] and release of radical oxygen species (ROS) [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation